Novel Variant Expands the Clinical Spectrum of CUX2-Associated Developmental and Epileptic Encephalopathies - Zhang, Feng; Li, Fuwei; Chen, Fujian; Huang, Jinrong; Luo, Qiong; Du, Xilong; Zhou, Jiapeng; Gu, Weiyue; Xu, Kaishou (Frontiers in Genetics, 2022)
Developmental and epileptic encephalopathies (DEE) caused by heterozygous deleterious variants in Cut Like Homeobox2(CUX2) is rare. To the best of our knowledge the only variant associated with a phenotype in this gene is the de novo missense variant c.1768G>A, p.Glu590Lys; however, further additional research is needed to characterize the relationship between disease and variants in this gene. In this study, we reported a patient from a non-consanguineous Chinese family presenting with epilepsy, developmental delay, and speech delay. Additionally, the patient responded well to levetiracetam, and at his last follow-up (5.5 years old), he had discontinued antiepileptic drug treatment and remained seizure-free for 6 months. To identify possible causative variants, trio-whole exome sequencing was performed. We identified a novel de novo missense CUX2 c.2834C>T, p. Thr945Met variant in the patient. Based on clinical and genetics information associated with the bioinformatics analyses, we hypothesized that this variant was the cause of the reported phenotype. AlphaFold and SWISS-MODEL homology modeling servers were used to predict the three‐dimensional (3D) structure of CUX2 protein. Predictions based on the 3D-structure modeling indicated that the p.Thr945Met substitution was likely to alter the DNA-binding specificities and affect protein function. On the basis of clinical characteristics and genetic analysis, we presented one case diagnosed with DEE67. Our finding expanded the clinical and molecular spectrum of CUX2 variants.